Association of Ki-67 Change Pattern After Core Needle Biopsy and Prognosis in HR+/HER2− Early Breast Cancer Patients - Li, Shuai; Chen, Xiaosong; Shen, Kunwei (Frontiers in Surgery, 2022)
Background: To investigate the association of Ki-67 change pattern after core needle biopsy (CNB) and prognosis in HR+/HER2- early breast cancer patients. Method: Eligible patients were categorized into three groups: Low group, Elevation group, and High group. Chi-square test and logistic regression analysis were used to compare the clinic-pathological characteristics. Kaplan-Meier method was used to estimate the rates of recurrence-free survival (RFS) and breast cancer-specific survival (BCSS), which were compared via Log-rank test. Cox proportional hazard analysis was performed to investigate independent prognostic factors. Results: A total of 2858 patients were included: 1179 (41.3%), 482 (16.9%), and 1197 (41.8%) patients were classified into the Low, Elevation, and High groups, respectively. Age, tumor size, histological grade, lymph-vascular invasion (LVI), and ER level status were associated with Ki-67 change pattern after CNB. With a median follow-up of 53.6 months, the estimated 5-year RFI rates for the Low group, Elevation, and High groups were 96.4%, 95.3% and 90.9%, respectively (P < 0.001). And 5-year BCSS rates were 99.3%, 98.3% and 96.8%, respectively (P = 0.001). Compared with patients in the Low group, patients in the High group had significantly worse RFI (hazard ratio [HR] 1.71, 95% confidence interval [CI] 1.16-2.54) in multivariate analysis. Conclusions: Ki-67 change after CNB was associated with prognosis in HR+/HER2- early breast cancer. Patients with Ki-67 high or elevation after CNB had an inferior disease outcome, indicating the necessity of re-evaluating Ki-67 on surgical specimens after CNB.